ANALYSIS OF THE APPLICATION OF ARTIFICIAL INTELLIGENCE-BASED DNA TESTS IN THE INVESTIGATION OF GENERAL CRIMES IN INDONESIA - Noprianto, Bachtiar (International Journal of Social Service and Research, 2024)
Investigating common crimes in Indonesia often faces challenges in proving them. DNA testing is internationally recognized as an accurate method of proof. However, its implementation in Indonesia is still hampered by limited health facilities and human resources, especially experts such as forensic scientists and law enforcement officials who are skilled in the use of forensic technology and analysis. With technological advancements, especially artificial intelligence, there is potential to improve the effectiveness of DNA testing in investigations. The purpose of this study is to evaluate the challenges in implementing artificial intelligence-based DNA tests in the investigation of common crimes in Indonesia and to identify strategic measures to overcome these barriers while maximizing the potential of this technology in law enforcement. The research method used is normative juridical, using a legal approach and an analytical approach. The findings of the study suggest that while artificial intelligence-based DNA testing has the potential to improve the effectiveness of investigations, significant challenges remain, including inadequate infrastructure, a lack of understanding among law enforcement officials, and the need for specialized training for forensic personnel. Furthermore, although Article 75 letter l of Law Number 35 of 2009 regulates the use of DNA tests, more detailed regulations are needed for the application of artificial intelligence in forensic analysis and evidence collection. AI-based DNA tests can improve the accuracy and efficiency of criminal investigations in Indonesia. Regulatory reform and collaboration between governments, educational institutions, and the private sector are needed to address the challenges and develop guidelines for their use.